Religious and Philosophical Meaning of Mythonyms in Russian Rock-Folk Music (Proceedings of Southern Federal University. Philology, 2019)
Victoria A. Goncharova, Anton A. Kochkin (Krasnodar, Russian Federation)The genre boundaries of modern music and literature have recently undergone significant changes that are connected with the appearance of a relatively new direction – rock music. A distinctive feature of this musical abstract is the presence of various sub-genre directions. One of these is folk rock music. The article presents an analysis of the meaning of mythonyms and theonyms in the cultural paradigm of folk music on the example of the work of the domestic folk-rock bands «The Melnitsa» and «The Nemnogo nervno». The process of studying the lyrics, reveals the correlation between the name of the text, represented by the mythonyms name, and the plot of the song in the context from which the mythonym (theonym) was borrowed. In the study the individual author’s transformation of the meaning of the myth is reflected and the religious and philosophical significance of onyms in the folk tradition is revealed.Key words: rock, folk-rock music, onomastics, metonymy, theonym, myth, mythologeme.DOI 10.23683/1995-0640-2019-4-80-88